(untitled) (Bangladesh Rice Journal, 2014)
This simulation study aimed to predict the effects of potential change of temperature and carbon dioxide on winter rice (Boro rice) production in Bangladesh. We assessed the effects of temperature and carbon dioxide on yield of Boro rice using DSSAT model for six major rice growing Agro- Ecological Zones (AEZs). The sensitivity analysis included variation of maximum and minimum temperature at 20C and 40C and different levels of CO2 concentrations (50 ppm, 100 ppm and 200 ppm) above the value reported in 2005 of IPCC Fourth Assessment Report (379 ppm). The model predicted that the change of maximum temperature drastically reduced rice yield at all selected locations. The average value of yield reductions (average percentage change of rice yield for 6 locations) of Boro rice were 6% and 16% for increasing maximum temperature at 20C and 40C respectively. Minimum temperature had also negative impacts on Boro rice yields that reduced yield by 4% for 20C and 8% for 40C. However, a slight increase in rice yield due to increase in CO2 concentration could not overcome the negative effect of temperature. Such yield reductions under changing climatic conditions could significantly affect the rice production in Bangladesh in future. DOI: http://dx.doi.org/10.3329/brj.v17i1-2.20897 Bangladesh Rice j. 2013, 17(1&2): 15-25